HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN KEMAMPUAN BERCERITA GURU PAUD SE-KECAMATAN KERINCI KANAN KABUPATEN SIAK (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research is backed by the storytelling ability of teachers related to interpersonal communication. Each teacher has a different level of storytelling that teachers should have to be active in speaking, accuracy in storytelling because the teacher must master the themes or topics to be told, proper gestures and mimics, and can change the mindset and feelings in each story. This research aims to know the relationship of interpersonal communication with the storytelling ability of PAUD teachers in Kerinci right district of Siak Regency. This research is quantitative research with the type of correlation study. The population of this research is the teacher of PAUD se-District Kerinci right of Siak regency which amounted to 60 teachers, samples of this research as many as 38 teachers taken using the formula Slovin. The data collection techniques used are observation and poll. Data analysis techniques using Person Product Moment correlation technique. Visible from the Keselurhan number of interpersonal communication indicators in the category quite well with a percentage of 60.4% while on the ability indicator of PAUD teacher storytelling in good category with a percentage of 75.73%. Based on the hypothesis test it is known from the value of correlation coefficient of rxy = 0.466 and the level of Siginifikansi 0,000 < 0.05. The level of relationship between interpersonal communication and the poverty of the PAUD teacher is included in the medium category with a coefficient of determination of 21.7%, meaning that interpersonal communication affects 21.7% of teacher's storytelling skills.Key Words : Interpsersonal Communication, Teacher Storytelling Ability